The Effect of Giving Vitamin D Supplements on Improving Ejection Fraction in Heart Failure Patients at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia - Andi Putra Siregar; Rukiah Chodilawati; Mgs. Irsan Saleh (HM Publisher, 2023)
Background: The role of vitamin D as an inflammation modulator, regulation system renin-angiotensin-aldosterone (RAAS), inhibits the production of parathyroid hormone (PTH), thereby causing left ventricular hypertrophy, causing hypocalcemia which induces hypertrophy in cardiac myocytes and can reduce cardiac contractility. This study aimed to determine the effect of giving vitamin D supplements on improving ejection fraction in heart failure patients at Dr. Mohammad Hoesin General Hospital (RSMH) Palembang, Indonesia. Methods: This study is an experimental study with a double-blind, randomized clinical trial design and uses primary data obtained from clinical examinations and supporting examinations of research subjects. A total of 40 research subjects participated in this study. Results: In this study, the median vitamin D level in the vitamin D supplementation group before treatment was 19.92 ng/dl (18.65-20.22), and in the placebo group was 19.74 ng/dl (18.14 - 20.13). After treatment with 1000 iu of vitamin D given for 3 months, the results showed that in the vitamin D supplementation group, there was an increase in vitamin D levels to 33.06 ng/dl (an increase of 13.14) with statistically significant results (p < 0 .05). In the vitamin D supplementation group, there was an increase in ejection fraction to 37.9% (an increase of 3.65%) with statistically significant results (p<0.05). Contrasting results were shown in the group that received a placebo, where there was a decrease in ejection fraction to 33.15% (2.25% decrease). Conclusion: There is an improving effect of giving vitamin D supplements on increasing ejection fraction in heart failure patients at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia.